Efficient synthesis of vitamin A palmitate in nonaqueous medium using self-assembled lipase TLL@apatite hybrid nanoflowers by mimetic biomineralization - Liqing Xu; Jianyun Yu; Anming Wang; Chengyi Zuo; Huimin Li; Xinxin Chen; Xiaolin Pei; Pengfei Zhang (Green Chemistry Letters and Reviews, 2018)
To conveniently prepare the immobilized enzyme for green synthesis of vitamin A palmitate, thermomyces lanuginosus lipase (TLL) was assembled with apatite derived from calcium phosphate in solution to form TLL@apatite hybrid nanoflowers (hNFs) by mimetic biomineralization. The obtained hNFs was characterized by SEM and applied in the enzymatic synthesis of vitamin A palmitate. Under optimal condition, when palmitic acid and vitamin A acetate were used as substrates, the yield of the target product was up to 90.4%, about 1.5 folds of that using free TLL. In addition, when each cycle for catalytic synthesis was carried out in petroleum ether with 20% water content as solvent for 12 h, the hNFs still retains 65.8% of initial catalytic synthetic ability after 10 cycles. These results demonstrated the hNFs was a kind of green biocatalyst with high catalytic activity and high stability with great potential in the green pharmaceuticals industry.